The combination of dimethoxycurcumin with DNA methylation inhibitor enhances gene re-expression of promoter-methylated genes and antagonizes their cytotoxic effect. Issue 10 (2nd October 2016) - Hassan, Hazem E.; Keita, Jean-Arnaud; Narayan, Lawrence; Brady, Sean M.; Frederick, Richard; Carlson, Samuel; C. Glass, Karen; Natesan, Senthil; Buttolph, Thomm; Fandy, Tamer E.
ABSTRACT: Curcumin and its analogs exhibited antileukemic activity either as single agent or in combination therapy. Dimethoxycurcumin (DMC) is a more metabolically stable curcumin analog that was shown to induce the expression of promoter-methylated genes without reversing DNA methylation. Accordingly, co-treatment with DMC and DNA methyltransferase (DNMT) inhibitors could hypothetically enhance the re-expression of promoter-methylated tumor suppressor genes. In this study, we investigated the cytotoxic effects and epigenetic changes associated with the combination of DMC and the DNMT inhibitor decitabine (DAC) in primary leukemia samples and cell lines. The combination demonstrated antagonistic cytotoxic effects and was minimally cytotoxic to primary leukemia cells. The combination did not affect the metabolic stability of DMC. Although the combination enhanced the downregulation of nuclear DNMT proteins, the hypomethylating activity of the combination was not increased significantly compared to DAC alone. On the other hand, the combination significantly increased H3K27 acetylation (H3K27Ac) compared to the single agents near the promoter region of promoter-methylated genes. Furthermore, sequential chromatin immunoprecipitation (ChIP) and DNA pyrosequencing of the chromatin-enriched H3K27Ac did not show any significant decrease in DNA methylation compared to other regions. Consequently, the enhanced induction of promoter-methylated genes by the combination compared to DAC alone is mediated by a mechanism that involves increased histone acetylation and not through potentiation of the DNA hypomethylating activity of DAC. Collectively, our results provide the mechanistic basis for further characterization of this combination in leukemia animal models and early phase clinical trials.